A three-dimensional hydroxyapatite/polyacrylonitrile composite scaffold designed for bone tissue engineering. Issue 4 (8th January 2018) - Wu, Shuyi; Wang, Jieda; Zou, Leiyan; Jin, Lin; Wang, Zhenling; Li, Yan
Abstract : A fluffy and porous (3D) HA composite fibrous scaffold was fabricated by employing an improved electrospinning technique combined with a bio-mineralization process. Abstract : In recent years, various composite scaffolds based on hydroxyapatite have been developed for bone tissue engineering. However, the poor cell survival micro-environment is still the major problem limiting their practical applications in bone repairing and regeneration. In this study, we fabricated a class of fluffy and porous three-dimensional composite fibrous scaffolds consisting of hydroxyapatite and polyacrylonitrile by employing an improved electrospinning technique combined with a bio-mineralization process. The fluffy structure of the hydroxyapatite/polyacrylonitrile composite scaffold ensured the cells would enter the interior of the scaffold and achieve a three-dimensional cell culture. Bone marrow mesenchymal stem cells were seeded into the scaffolds and cultured for 21 days in vitro to evaluate the response of cellular morphology and biochemical activities. The results indicated that the bone marrow mesenchymal stem cells showed higher degrees of growth, osteogenic differentiation and mineralization than those cultured on the two-dimensional hydroxyapatite/polyacrylonitrile composite membranes. The obtained results strongly supported the fact that the novel three-dimensional fluffy hydroxyapatite/polyacrylonitrile composite scaffold had potential application in the field of bone tissue engineering.